Exploring momfluencers ethics as social media micro-influencer in Indonesia - Ratnasari, Eny; Rohnulyanti, Hanim; Hafiar, Hanny; Wada, Ibrahim (Universitas Padjadjaran, 2024)
Background: The tight business competition in Indonesia has made branding practitioners develop the most effective strategy to increase brand awareness by collaborating with influencers. In Indonesia, the number of influencers increases annually. One of the biggest is Insta-moms, mom influencers, or momfluencers. Momfluencers have challenges to ensure that their content does not violate ethics, such as advertising rules, and does not mislead the audience. Unfortunately, their lack of awareness of influencer ethics lets them create content based on briefs from clients or management and rely on their common sense. Purpose: This study aimed to analyze the contents of momfluencers, as micro-influencers, through an ethical perspective. Methods: We conducted a quantitative content analysis of 569 posts from 12 momfluencers. Results: Momfluencers’ posts predominantly consist of commercial content in videos or reels featuring influencer portraits with long descriptions. Ethically, momfluencers fail to meet the ethical norms. Aspects that have not been fulfilled are interaction with the audience, respect, participatory activities, social responsibility, connectedness, and loyalty. Meanwhile, aspects that have been fulfilled are trustworthiness, expertise or credibility, appearance, content quality, and communication quality. This study also found two potential ethics violations of momfluencer, engagement bias, and sharenting. Conclusion: Influencers have become an industry. Normalizing unethical practices due to a lack of information should be avoided. Influencer management and influencers under their auspices should know what is permissible and impermissible in their roles. Although there is no code of ethics for influencers in Indonesia, rules for public relations, journalism, and advertising can be a guide. Implications: The results of this study could be an evaluation for influencers in Indonesia and can be input for formulating an influencer code of ethics in Indonesia.